Wittgenstein and democratic politics
1 online resource
Keywords: "This volume demonstrates how Wittgenstein's philosophy can illuminate our understanding of politics and open new ways of conceptualizing democratic theory and practice. Its focus is on language, reason and communication as central to identifying present confusions in our understanding of democracy. The book seeks to engage Wittgenstein's philosophical insights, aiming to go beyond the dichotomous oppositions and conceptual entanglements pervading existing frameworks of social and political theories of democracy. Its key topic is the irreplaceable role of dialogue in civic democratic engagement as a condition for the understanding of self and others and, hence, for political life in which reason has a role. Indeed, it presents concrete examples of how Wittgenstein can be constructively applied to current political discourse. Part I of the volume focuses on the general idea of applying Wittgenstein's philosophy to political and democratic theory and explains the deep and intrinsic relation between Wittgenstein's thought and politics. Part II discusses Wittgenstein's concrete concepts as illuminating for understanding selected aspects of democratic politics. Part III deals with a possible exchange between Wittgenstein and other political thinkers, especially Hannah Arendt. Wittgenstein and Democratic Politics will appeal to researchers and advanced students working on Wittgenstein's philosophy, political philosophy, and democratic theory"--